Temperature Regulation of Photovoltaic Module Using Phase Change Material: A Numerical Analysis and Experimental Investigation - Mahamudul, H.; Rahman, M.M.; Metselaar, H.S.C.; Mekhilef, Saad; Shezan, S.A.; Sohel, R.; Sayuti, Mohd; Badiuzaman, W.N.I. (Hindawi Publishing Corporation, 2016)
This work represents an effective design of a temperature regulated PV module by integrating phase change materials for Malaysian weather condition. Through the numerical analysis and experimental investigation it has been shown that if a PCM layer of width 0.02 m of RT 35 is used as a cooling arrangement with a PV module, the surface temperature of the module is reduced by 10°C, which remains constant for a period of 4–6 hours. This reduction of temperature implies the increase in conversion efficiency of the module. Experiment as well as investigation has been carried out considering typical Malaysian weather. Obtained result has been validated by using experimental prototype and comparative analysis.